PROSPECTS FOR THE INTRODUCTION OF INNOVATIVE TECHNOLOGIES IN THE DEVELOPMENT OF THE AGRO-INDUSTRIAL COMPLEX OF UKRAINE - Garafonova , Olga; Marhasova, Viktoriya (Socio-economic relations in the digital society, 2022)
The article examines the prospects for introducing innovative technologies for the development of the agro-industrial complex. The main attention is paid to the analysis of the possibilities of using 5G in the agro-industrial complex, the technical advantages of 5G communication in the agro-industrial complex, which ensure precision farming, are compared with current 4G technologies. Empirical evidence has shown that the 5G connection is currently being tested in 5 out of 6 5G Testing cases and demonstrates the potential for future applications in other use scenarios, mainly applications. The geographical distribution is global, although it is concentrated in the northern hemisphere, which indicates that the application for developing countries is not yet applicable at all or little. The future of 5G in the agro-industrial complex will also depend on a number of contributing factors that will determine the implementation of digital innovations within the broader topic. Although innovations are sometimes driven by new technologies themselves, they are often driven by bottlenecks faced by various participants in the food system. In some cases, the bottleneck is high labor costs or the need to increase productivity to increase farm profits, while in other cases, environmental pressures can accelerate the development and introduction of new communication technologies. For telecommunications companies and governments, sparsely populated rural areas, the need to eliminate social differences and deliver public goods to a particular region may lead to the promotion of 5G as a prospect for the introduction of innovative technologies for the development of the agro-industrial complex.